The role of thrombin in early-onset seizures - Savotchenko, Alina; Klymenko, Mariia; Shypshyna, Mariia; Isaev, Dmytro (Frontiers in Cellular Neuroscience, 2023)
A variety of clinical observations and studies in animal models of temporal lobe epilepsy (TLE) reveal dysfunction of blood-brain barrier (BBB) during seizures. It is accompanied by shifts in ionic composition, imbalance in transmitters and metabolic products, extravasation of blood plasma proteins in the interstitial fluid, causing further abnormal neuronal activity. A significant amount of blood components capable of causing seizures get through the BBB due to its disruption. And only thrombin has been demonstrated to generate early-onset seizures. Using the whole-cell recordings from the single hippocampal neurons we recently showed the induction of epileptiform firing activity immediately after the addition of thrombin to the blood plasma ionic media. In the present work, we mimic some effects of BBB disruption in vitro to examine the effect of modified blood plasma artificial cerebrospinal fluid (ACSF) on the excitability of hippocampal neurons and the role of serum protein thrombin in seizure susceptibility. Comparative analysis of model conditions simulating BBB dysfunction was performed using the lithium-pilocarpine model of TLE, which most clearly reflects the BBB disruption in the acute stage. Our results demonstrate the particular role of thrombin in seizure-onset in conditions of BBB disruption.